Labirintos da gramática - tempo, figuração e subjetividade nas Philosophische Bemerkungen - Michetti, Gustavo Gueraldini (Universidade Federal de São Carlos, 2024)
This thesis examines the role that temporality and subjectivity perform in the reformulation of the concept of propositional picture at the beginning of Wittgenstein’s Middle philosophy, especially in the “typescript” Ts 209 (1930), published after Wittgenstein's death under the name Philosophische Bemerkungen. More precisely, the objective is to understand to what extent the ideas of “intention” and “figuration” – which characterize the very function of language and proposition – develop from problems related to “time” and the “self”. At first, this thesis analyzes is the difficulty of reconciling two essentially distinct fields: On the one hand, language is structured by the forms of physical temporality, which involves the ideas of the past, present and future; on the other hand, which our propositions must represent, the phenomena, are structured by phenomenological temporality, determined by the characteristics of the instant, flow and succession (before-after). Secondly, this study is dedicated to exploring the possibilities of figurating phenomena based on this temporal mismatch between the physical form of language and the form of experience, taking into account the concept of expectation developed in chapters II-IV of Bemerkungen. Thirdly, the thesis explores the contrast between first-person singular and third-person singular pronouns, bearing in mind to discuss the issues of subjectivity and alterity in Wittgenstein. This work argues that, in Bemerkungen, there is a “grammatical asymmetry” between the present and other temporal perspectives, as well as between the “I” and the “other pronouns”; an asymmetry that underlies the concept of figurativity and can characterize a discursive dimension of language.
Labyrinths of grammar - time, picture, and subjectivity in Philosophische Bemerkungen
Keywords: Wittgenstein; Tempo; Subjetividade; Gramática; Figuração; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA